2022
DOI: 10.1109/access.2022.3206357
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of Self-Shielded MRI Gradient Coils With Finite Track Width

Abstract: Gradient coils are essential for the performance of the MR imaging system. Usually, coils are designed assuming thin wire tracks. Here, we design an MR gradient coil set using a more general approach considering the exact track width using the discrete wire approach. The effect of track width on the DC current density distribution and resultant magnetic fields using both loop and Golay coils are first demonstrated. Both, self-shielded X and Z gradient coils of definite width/thickness are designed and optimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…TMIM is a more general approach that we managed to implement at acceptable computational efficiency compared to Ansys. We preliminary applied and validated TMIM using our computational framework for a transverse gradient coil, as shown in Alsharafi et al 55 An agreement is shown in the result of transient analysis for the three methods (see Figure 7B). The distortion of the gradient field waveform is evident and attributed to the induced eddy currents on the cryostat.…”
Section: Memory No Of Elements Simulation Time (All Frequencies) Simu...mentioning
confidence: 84%
See 4 more Smart Citations
“…TMIM is a more general approach that we managed to implement at acceptable computational efficiency compared to Ansys. We preliminary applied and validated TMIM using our computational framework for a transverse gradient coil, as shown in Alsharafi et al 55 An agreement is shown in the result of transient analysis for the three methods (see Figure 7B). The distortion of the gradient field waveform is evident and attributed to the induced eddy currents on the cryostat.…”
Section: Memory No Of Elements Simulation Time (All Frequencies) Simu...mentioning
confidence: 84%
“…TMIM is a more general approach that we managed to implement at acceptable computational efficiency compared to Ansys. We preliminary applied and validated TMIM using our computational framework for a transverse gradient coil, as shown in Alsharafi et al 55 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations